2023
DOI: 10.3389/fpsyt.2023.1139946
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and variables associated with depression, anxiety, and stress among Chilean higher education students, post-pandemic

Abstract: BackgroundMental health among university students is a public health problem in Chile, understanding that this population is susceptible to mental disorders.ObjectiveThe present study aimed to determine the prevalence and variables influencing depression, anxiety, and stress in Chilean university students.MethodA representative sample (n = 1,062) of Chilean university students and a cross-sectional study design were used. Bivariate analysis and multiple logistic regression were performed to identify risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
(76 reference statements)
1
4
0
1
Order By: Relevance
“…Studies in Chile ( 33 ), Bangladesh ( 34 ), and Palestine ( 35 ) using the same mental health questionnaire as our study found a much higher prevalence of symptoms of depression, anxiety, and stress. However, all these studies collected data through online questionnaires, which will make the study participants non-representative.…”
Section: Discussionsupporting
confidence: 66%
“…Studies in Chile ( 33 ), Bangladesh ( 34 ), and Palestine ( 35 ) using the same mental health questionnaire as our study found a much higher prevalence of symptoms of depression, anxiety, and stress. However, all these studies collected data through online questionnaires, which will make the study participants non-representative.…”
Section: Discussionsupporting
confidence: 66%
“…Este resultado se vincula con hallazgos previos (Bantjes et al, 2023). En este sentido, se debe incluir una serie de factores intervinientes que podrían ser analizados y evaluados según las características de cada territorio, como el género, pertenencia a minorías sexuales, dedicarse exclusivamente a actividades académicas y tomar medicamentos recetados (Martínez-Líbano et al, 2023). Todo lo cual aporta a la creación de orientaciones universitarias que considera las particularidades de cada actor que integran las comunidades educativas de El Salvador.…”
Section: Discussionunclassified
“…The isolation, social distance, and loss of personal freedom during the COVID-19 pandemic may have exacerbated students' anxiety and stress (Martínez-Líbano et al, 2023). These changes might have led to students' uneasiness in adapting to the new learning environment, increased anxiety in the classroom, and activated stress signals (Buizza et al, 2022;, thereby resulting in impaired academic performance and socioeconomic status (3).…”
Section: Anxietymentioning
confidence: 99%